Training Midwives And Health Cadres Improves Their Proficiency With MCH Books - Indrasari, Nelly (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2024)
The Maternal and Child Health Book (MCH Books) has been launched as a crucial instrument for tracking both maternal and child health as well as child growth and development in an effort to improve the caliber of maternity and child health services in Indonesia.However, health professionals, particularly midwives and health cadres who deal directly with the community, particularly pregnant women, postpartum mothers, infants, toddlers, and preschoolers, must have a thorough comprehension of the MCH Books and possess a few specific abilities in order to use them to their fullest potential. The purpose of this community service project is to assess the effects of the MCH Book usage training that was provided to 30 health cadres and one midwife.Participants learn how to fill out, comprehend, and use data from the MCH Book for more focused health interventions and to support moms and children through intense, interactive, and case-based training approaches. The knowledge and abilities of midwives and health cadres have significantly increased following training, according to community service outcomes. Over 98% of participants reported feeling more comfortable utilizing the MCH Book and putting it to use in their regular practice.The community's feedback also revealed that following the training, midwives and health cadres were able to provide better counseling and information. Sixty ideas were received from pregnant women, maternity mothers, postpartum mothers, newborns, toddlers, and preschoolers. The study concludes that providing midwives and health cadres with training on the use of MCH Books has increased their knowledge and proficiency. This demonstrates how crucial it is to fund frontline healthcare professionals' ongoing education and training in order to raise the standard of public health services.